Bermain Edukatif Ular Tangga Mampu Mengatasi Kecemasan pada Anak Hospitalisasi - Padila Padila; Juli Andri; Muhammad Bagus Andrianto; Andry Sartika; Yesi Oktaviyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of snake and ladder educational game therapy (APE) on reducing anxiety in hospitalized children. This study uses an experimental method with a one-group pre-post test design. The results showed that the average level of anxiety before playing snake and ladder therapy in treated children was 19.13 with moderate anxiety category. The rate after snake therapy in treated children was 14.20 with a mild grade. In conclusion, snake and ladder play therapy reduces anxiety levels in hospitalized children. Keywords: Hospitalization, Educational Game (APE) Snakes and Ladders, Children's Anxiety Level